Simplicispira lacusdiani sp. nov., a novel betaproteobacterium isolated from a freshwater reservoir. Issue 1 (15th November 2018) - Shi, Yun-Lei; Sun, Ye; Jiang, Zhu-Ming; Ruan, Zhi-Yong; Su, Jing; Yu, Li-Yan; Zhang, Yu-Qin
Abstract : A Gram-stain-negative, motile, rod-shaped bacterium, designated CPCC 100842 T, was isolated from a freshwater reservoir in south-west China. The 16S rRNA gene sequence comparison of strain CPCC 100842 T with the available sequences in the GenBank database showed that the isolate was closely related to members of the family Comamonadaceae, with the highest similarities to Simplicispira metamorpha DSM 1837 T (98.05 %), Simplicispira limi KCTC 12608 T (97.86 %), Simplicispira psychrophila LMG 5408 T (97.04 %) and Simplicispira piscis JCM 19291 T (97.0 %). In the phylogenetic tree based on 16S rRNA gene sequences, strain CPCC 100842 T formed a distinct phylogenetic subclade within the genus Simplicispira . The major cellular fatty acids were as C16 : 0 and summed feature 3 (C16 : 1 ω 7 c /C16 : 1 ω6 c ). Q-8 was detected as the only respiratory quinone. Phosphatidylethanolamine, phosphatidylglycerol, diphosphatidylglycerol, aminophospholipid and glycolipid were found in the polar lipid extraction. The genomic DNA G+C content was 67.4 mol%. The average nucleotide identity value was 80.4 % by comparing the draft genome sequences of strain CPCC 100842 T and S. metamorpha DSM 1837 T . The DNA–DNA hybridization result between strain CPCC 100842 T and S. metamorpha DSM 1837 T showed 37±3 % genomic relatedness. On the basis of the genotypic analysis and phenotypic characteristics, we propose that strain CPCC 100842 T represents a novel species of the genus Simplicispira in the family Comamonadaceae with the name Simplicispira lacusdiani sp. nov. Strain CPCC 100842 T (=KCTC 52093 T =DSM 102231 T ) is the type strain of the species.